(untitled) - Food and Agriculture Organization of the United Nations (Tashket, Uzbekistan, 2008)
The Workshop, attended by stakeholders from Kazakhstan, Kyrgyzstan, Tajikistan, Turkey and Uzbekistan, recognized that the Code provides a suitable framework and guide for environmentally compatible, socially acceptable and economically viable development and management of the fisheries sector in the Central Asian region. It was noted that some of the countries in the region (e.g. Kyrgyzstan, Tajikistan and Uzbekistan) are using the Code as guidance in their policy and legal framework development.
Keywords: Fisheries,Central Asian Region,Thủy sản,Khu vực Đông Á